SAT0454 In A Two-Year Double-Blind Randomized Controlled Multicenter Study, Chondroitin Sulfate Was Significantly Superior To Celecoxib at Reducing Cartilage Loss with Similar Efficacy at Reducing Disease Symptoms In Knee Osteoarthritis Patients. (15th July 2016) - Pelletier, J.P.; Raynauld, J.P.; Beaulieu, A.; Bessette, L.; Morin, F.; Brum-Fernandes, A.J.; Abram, F.; Dorais, M.; Martel-Pelletier, J.
Abstract : Background: In osteoarthritis (OA) treatment, although chondroitin sulfate (CS) was found in a number of studies using radiography to have a structure modifying effect, to date the question is still under debate. A clinical study using quantitative magnetic resonance imaging (qMRI) is therefore of the utmost importance. Objectives: The present study has the objective to explore, as the first aim, in a two-year randomized, controlled double-blind clinical study using qMRI, the disease modifying effect of CS treatment versus celecoxib (CE) on cartilage volume loss (CVL) in knee OA. The second aim was to investigate and compare the effect of CS and CE on symptoms. Methods: Symptomatic primary knee OA patients according to ACR criteria with Kellgren-Lawrence grades 2–3 and synovitis were included and treated with CS (1200 mg a day) or CE (200 mg once daily) for 24 months. Patients at high risk for cardiovascular and/or gastrointestinal disease were not included. MRI was performed at baseline, 12 and 24 months. CVL, bone marrow lesion (BML) size, and synovial membrane thickness were evaluated using qMRI, and presence of joint swelling and effusion clinically evaluated. Clinical symptoms were also assessed by validated questionnaires. Results: In the intention-to-treat analysis (n=194), patients treated with CS had reduced CVL at 24 months in the medial compartment (p=0.026) and condyle (p=0.008) compared to celecoxib. In the completer analysis, CS reduced CVL in the medial compartment at 12 months (p=0.026) and medial compartment and condyle at 24 months (p=0.030, p=0.010). A trend toward a reduced (p=0.070) synovial thickness in the medial suprapatellar bursa was observed in CS patients. Both treatment groups experienced a marked reduction in incidence of patients with joint swelling/effusion and in symptoms (WOMAC total, pain, and function, and VAS pain) over time. Data showed similar good safety profiles for both drug treatments. Conclusions: This trial demonstrated, for the first time, the superiority of CS over CE at reducing the long term progression of knee OA structural changes. Moreover, both drugs were found equally effective at reducing the symptoms of OA. These findings have important implications regarding the usefulness of CS for long term management of knee OA and its impact on disease outcome. Disclosure of Interest: J. P. Pelletier Shareholder of: Arthrolab Inc., Grant/research support from: Bioiberica, Consultant for: Bioiberica, Speakers bureau: Bioiberica, J. P. Raynauld: None declared, A. Beaulieu: None declared, L. Bessette: None declared, F. Morin: None declared, A. J. Brum-Fernandes: None declared, F. Abram: None declared, M. Dorais: None declared, J. Martel-Pelletier Shareholder of: Arthrolab Inc., Grant/research support from: Bioiberica, Consultant for: Bioiberica